2019
DOI: 10.1371/journal.pone.0226164
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA signatures in monozygotic twins discordant for congenital heart defects

Abstract: BackgroundMicroRNAs (miRNAs) are small RNAs regulating gene expression post-transcriptionally. Recent studies demonstrated that miRNAs are involved in the development of congenital heart defects (CHD). In this study, we aimed at identifying the specific patterns of miRNAs in blood of monozygotic twin pairs discordant for CHD and to assess whether miRNAs might be involved in the development or reflect the consequences of CHD.MethodsmiRNA microarray analysis and Real-Time Quantitative PCR (RT-qPCR) were employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…DataAssist TM Software v3.0 (Applied Biosystems) was used to calculate the relative abundance changes of miRNAs by the equation 2 − Ct with RNAU6B serving as an endogenous control as previously used and validated for this type of sample (21,23,24,(26)(27)(28)(29)(30)(31). Adjustment for multiple testing was performed by controlling the false discovery rate (FDR) according to the approach of Benjamini and Hochberg (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DataAssist TM Software v3.0 (Applied Biosystems) was used to calculate the relative abundance changes of miRNAs by the equation 2 − Ct with RNAU6B serving as an endogenous control as previously used and validated for this type of sample (21,23,24,(26)(27)(28)(29)(30)(31). Adjustment for multiple testing was performed by controlling the false discovery rate (FDR) according to the approach of Benjamini and Hochberg (32).…”
Section: Discussionmentioning
confidence: 99%
“…These platforms contain probes for the detection of 2,549 human miRNAs. An input amount of 100 ng of isolated RNA including miRNAs was labeled and subsequently hybridized to the miRNA microarray chip and the procedure was completed as previously described ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…After loading, the array was placed in the Biomark HD instrument for quantification and detection using a specific thermal cycling protocol for either miRNA or mRNA analysis. RNAU6B and GAPDH were used as reference endogenous controls for miRNA and mRNA, respectively, as previously recommended for this type of sample [ 14 , 15 , 16 , 17 , 18 , 19 , 21 , 26 ]. The data were analyzed with Real-Time PCR Analysis Software (Fluidigm Corporation), according to Fluidigm’s recommendation.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, there are 2300 “real” miRNAs in the miRNA database based on miRBase.org [ 13 ]. It is assumed, that almost every cellular and biological process is regulated by miRNAs, including processes regulating CHDs [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Study showed that the MTHFR genotype/diet combination and BMI were significantly associated with LINE-1 methylation in mothers of children with DS/ CHD + [5]. Recently, micro-RNA signatures discordant for CHD in monozygotic twins were observed [112].…”
Section: Epigenetic Genetic and Nutrigenomic Risk Factors For Congementioning
confidence: 99%